Feeling mediated : a history of media technology and emotion in America - Malin, Brenton J., 1972- (Critical cultural communication., 2014)
New technologies, whether text message or telegraph, inevitably raise questions about emotion. New forms of communication bring with them both fear and hope, on one hand allowing us deeper emotional connections and the ability to forge global communities, while on the other prompting anxieties about isolation and over-stimulation. Feeling Mediated investigates the larger context of such concerns, considering both how media technologies intersect with our emotional lives and how our ideas about these intersections influence how we think about and experience emotion and technology themselves.